Canine isosporosis: A neonatal clinical approach - Dos Santos Reginaldo, Gisele Moraes [UNESP]; Martins Dos Reis, Gisele Fabrícia; Baptista Galvão, André Luiz; Nery Loiola, Saulo Hudson; Gomes, Jancarlo Ferreira; Dourado Coelho, Willian Marinho; Saraiva Bresciani, Katia Denise [UNESP] (Universidade Estadual de Londrina, 2019)
Acute diarrhea in young dogs is among the main complaints described by tutors in veterinary services. Complications related to water and electrolyte imbalances due to intestinal alterations can compromise homeostasis in these pups, mainly due to dehydration. Consequently, they do not present a satisfactory clinical response and are exposed to the risk of early death. Among the different types of diarrhea, the infectious diarrhea due to viruses, bacteria, and parasites are particularly significant. Coccidia of the genus Isospora (Cystoisospora spp.) is an important intestinal pathogen that causes severe clinical manifestations in puppies. Since high parasitic loads render these puppies highly susceptible to opportunistic infections, coccidia infection may cause impaired corporal and cognitive development and even lead to death. Studies regarding this issue, particularly concerning clinical knowledge in neonatology, are scarce in veterinary medicine. Thus, in this study, we intend to discuss the enteric alterations and the most commonly used current diagnostic techniques, as well as to analyze effective therapeutic and prophylactic proposals.
Keywords: Cystoisospora spp; Diarrhea; Enteritis; Pups